A composite electrode material for electrochemical desalination and a preparation method and application thereof

CN121494151BActive Publication Date: 2026-11-03XIAN JIAOTONG LIVERPOOL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511779071.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-28
Publication Date
2026-11-03
Estimated Expiration
2045-11-28

AI Technical Summary

Technical Problem

现有CDI技术中,法拉第材料与MXene表面库仑排斥效应导致界面相容性差,传统改性剂影响活性位点,合成工艺高温导致电导率下降,材料稳定性和导电性不足。

Method used

By coating Faraday materials with conductive polymers and self-assembling with MXene to form a charge-matched composite structure, an in-situ conductive network is constructed. The interfacial bonding force is enhanced through electrostatic forces and hydrogen bonding, and internal stress is buffered, enabling low-temperature controllable synthesis.

Benefits of technology

It significantly improves desalination capacity and cycle stability, and the material properties combine high conductivity, structural stability and fast ion transport, making it suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121494151B_ABST
    Figure CN121494151B_ABST
Patent Text Reader

Abstract

The application provides a composite electrode material for electrochemical desalination and a preparation method and application thereof, the composite electrode material comprising an electrically conductive polymer coated Faraday material and a MXene material, and the electrically conductive polymer coated Faraday material and the MXene material are self-assembled through electrostatic force. The composite electrode material provided by the application realizes charge matching molecular level compounding and in-situ construction of an electrically conductive network, significantly improves the desalination capacity and cycle stability of the composite material when used for electrochemical desalination; and the preparation method provided by the application is simple, can realize low-temperature controllable synthesis of the material, and is suitable for large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of capacitive deionization technology, and relates to a composite electrode material for electrochemical desalination, its preparation method and application. Background Technology

[0002] Capacitive deionization (CDI), as an emerging electrochemical water treatment technology, has demonstrated significant application value in seawater desalination, brackish water desalination, and industrial wastewater treatment due to its advantages such as low energy consumption (<2V), environmental friendliness, and ease of operation. Compared to traditional desalination technologies (such as reverse osmosis, thermal distillation, and electrodialysis), CDI technology drives the directional migration of ions in the solution to the electrode surface through the application of an electrostatic field, achieving efficient adsorption. Electrode regeneration can be achieved after the electric field is removed. This unique "adsorption-desorption" mechanism eliminates the need for high pressure or high temperature conditions, significantly reducing energy consumption and operating costs, resulting in significant economic and environmental benefits.

[0003] The core performance of CDI technology lies in the design of the electrode material system. Early research was mainly based on carbon-based materials with double-layer mechanism (such as activated carbon and graphene), but their desalination capacity was generally limited to 10~20 mg / g. In recent years, electrode materials based on Faraday reaction (such as Prussian blue analogs, transition metal oxides and sodium superionic conductors) have become a research hotspot due to their high theoretical capacity (>100 mg / g). However, these materials still face three major challenges in practical applications: (1) poor intrinsic conductivity leads to limited charge transport; (2) insufficient structural stability during cycling; and (3) significant volume effects associated with ion insertion / extraction.

[0004] To address the aforementioned issues, researchers have proposed a strategy of combining two-dimensional transition metal carbides (MXenes) with Faraday materials. For example, constructing a sandwich structure (CN119285047A) with Prussian blue for MXene improves conductivity; in-situ growth of NaTi2(PO4)3 on the MXene surface (CN119285047A) enhances specific capacity and adsorption capacity; and developing MXene / polyaniline heterostructures (CN119191482A) extends cycle life. However, existing composite technologies still face key technical challenges. For instance, most Faraday materials and MXene surfaces are negatively charged, leading to Coulomb repulsion and poor interfacial compatibility. Some studies utilize traditional surface modifiers (such as CTAB) to modify the components, but this sacrifices some active sites. Furthermore, the preparation process has defects; for example, hydrothermal methods (>120℃) can cause MXene oxidation, resulting in a significant decrease in conductivity.

[0005] Therefore, developing novel interface engineering strategies to achieve: (1) charge-matched molecular-level composites; (2) in-situ construction of conductive networks; and (3) low-temperature controllable synthesis will be key to breaking through existing technological bottlenecks. This requires starting from the chemical essence of the material's surface and interface, establishing a structure-property relationship, and providing new ideas for developing efficient and stable CDI electrode materials. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the present invention aims to provide a composite electrode material for electrochemical desalination, its preparation method, and its applications. In the composite electrode material provided by the present invention, the conductive polymer, Faraday material, and MXene material work synergistically to achieve charge-matched molecular-level composite and in-situ construction of a conductive network, significantly improving the desalination capacity and cycle stability of the composite material during electrochemical desalination. Furthermore, the preparation method provided by the present invention is simple, enabling low-temperature controllable synthesis of the material, making it suitable for large-scale applications.

[0007] To achieve this objective, the present invention adopts the following technical solution:

[0008] In a first aspect, the present invention provides a composite electrode material for electrochemical desalination, the composite electrode material comprising a conductive polymer-coated Faraday material and an MXene material, wherein the conductive polymer-coated Faraday material and the MXene material achieve self-assembly through electrostatic interaction.

[0009] In this invention, Faraday materials and conductive polymers can enhance interfacial bonding through surface hydrogen bonding, forming a stable composite structure. Simultaneously, because the conductive polymer coats the surface of the Faraday material, it provides a positively charged surface chemical environment, allowing it to self-assemble with negatively charged MXene materials via electrostatic forces, resulting in a structurally stable and homogeneous composite material. Compared to existing technologies that modify the surface of Faraday materials to composite with MXene materials, this invention uses conductive polymer coating to solve the problems of low intrinsic conductivity and poor stability of Faraday materials. The in-situ polymerized conductive polymer forms a uniform, positively charged conductive coating layer on the surface of Faraday nanoparticles, establishing an extremely short-range electron extraction channel for the Faraday material. Furthermore, the flexible conductive polymer layer surrounding the Faraday material effectively absorbs and buffers the internal stress generated during sodium ion insertion / extraction, preventing the active material from pulverizing and detaching. This solves the long-standing technical challenge of traditional surface modification methods failing to simultaneously achieve high conductivity, excellent structural stability, and rapid ion transport.

[0010] In this invention, the Faraday material is the core active substance, providing active sites for adsorbing salt ions through redox reactions, thus determining the basic desalination capacity and ion selectivity. The conductive polymer optimizes the surface chemical environment of the Faraday material and improves ion transport channels. The conductive polymer not only provides the Faraday material with a positively charged surface but also possesses redox activity, increasing the electrochemical adsorption sites and capacity. The MXene material can self-assemble with the conductive polymer via electrostatic forces to construct a three-dimensional conductive network, improving electron transport efficiency and strengthening structural support. The synergistic effect of these three components significantly improves the desalination capacity and cycle stability of the composite material when used for electrochemical desalination.

[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The technical objectives and beneficial effects of the present invention can be better achieved and realized through the following preferred technical solutions.

[0012] Preferably, the MXene material comprises Ti3C2T x MXene, Ta4C3T x MXene, Ti2CT x MXene, Nb4C3T x MXene, Nb2CT x MXene, V2CT x MXene or Mo2CT x Any one or at least two combinations of MXene, where T x It is a functional group, including any one of -O, -OH, -F or -Cl.

[0013] Preferably, the conductive polymer comprises any one or a combination of at least two of polyaniline, polypyrrole, or poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid), and more preferably polyaniline.

[0014] Preferably, the Prussian blue comprises any one or a combination of at least two of Na2Mn[Mn(CN)6], Fe4[Fe(CN)6]3, or Na2M[Fe(CN)6], wherein the M in Na2M[Fe(CN)6] comprises any one or a combination of at least two of Ni, Cu, Zn, or Fe.

[0015] Preferably, the mass ratio of the conductive polymer-coated Faraday material to the MXene material is (1~3):1, for example, 1:1, 1.5:1, 2:1, 2.5:1 or 3:1.

[0016] In this invention, the ratio is set based on the following considerations: When the ratio is below 1:1 (i.e., the MXene content is too high), although the electrode conductivity is further improved, too much of the active material mass percentage is sacrificed, resulting in a significant decrease in the overall energy density of the electrode; when the ratio is above 3:1 (i.e., the MXene content is too low), MXene cannot form a complete and continuous three-dimensional conductive network, resulting in some active materials not being effectively utilized, and the rate performance and cycle stability of the electrode deteriorate sharply. Within the range of (1~3):1, the composite material can simultaneously achieve high conductivity, high active material utilization, optimized ion transport channels, and excellent structural stability, thereby realizing a synergistic improvement in high capacity, high rate capability, and long cycle life.

[0017] Preferably, in the conductive polymer-coated Faraday material, the coating thickness of the conductive polymer is 4nm~9nm, for example, 4nm, 5nm, 6nm, 7nm, 8nm or 9nm.

[0018] In this invention, by controlling the coating thickness of the conductive polymer within the aforementioned range, the coating layer is guaranteed to have continuous and stable high conductivity (thickness ≥ 4 nm), providing an efficient electron extraction path for the active material. Its ultra-thin characteristics (thickness ≤ 9 nm) ensure that sodium ions can shuttle extremely quickly without obstruction, thereby guaranteeing the material's excellent high-rate performance. At the same time, the coating layer of this thickness has both good flexibility and strength, which can effectively buffer the volume changes of the active material during cycling and extend its lifespan. However, if the coating layer is too thick, it will increase the inactive mass, easily hinder ion transport, and reduce energy density, resulting in a decline in material performance.

[0019] In a second aspect, the present invention provides a method for preparing a composite electrode material for electrochemical desalination as described in the first aspect. The preparation method includes: initiating the polymerization of conductive polymer monomers on the surface of a Faraday material through an in-situ polymerization reaction to obtain a Faraday material coated with a conductive polymer, then performing a first mixing with an MXene material, and finally self-assembling the composite electrode material under electrostatic force.

[0020] Preferably, the in-situ polymerization reaction includes: firstly, mixing the Faraday material and an acidic solution to obtain a second mixture, and then sequentially mixing the mixture with a conductive polymer monomer and an oxidant solution to obtain the conductive polymer-coated Faraday material after the in-situ polymerization reaction.

[0021] Preferably, the Faraday material comprises any one or a combination of at least two of sodium titanium phosphate, titanium phosphate, titanium pyrophosphate, sodium aluminum titanium phosphate, sodium vanadium phosphate, or Prussian blue, and more preferably sodium titanium phosphate.

[0022] Preferably, the acidic solution comprises an acid and a solvent.

[0023] Preferably, the acid includes any one or a combination of at least two of hydrochloric acid, phytic acid, or p-toluenesulfonic acid.

[0024] Preferably, the solvent includes water, ethanol, water, and any one of ethanol or acetonitrile.

[0025] Preferably, the conductive polymer monomer includes any one or a combination of at least two of aniline, pyrrole, or styrene sulfonic acid / 3,4-ethylenedioxythiophene.

[0026] Preferably, the oxidant solution comprises an oxidant and water, wherein the oxidant comprises ammonium persulfate and / or ferric chloride.

[0027] Preferably, the mass ratio of the conductive polymer monomer to the Faraday material is (2~4):1, for example, 2:1, 2.5:1, 3:1, 3.5:1 or 4:1.

[0028] Preferably, the molar ratio of the oxidant to the conductive polymer monomer is 1:(1~2), such as 1:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1 or 2:1, etc.

[0029] Preferably, the average particle size of the sodium titanium phosphate is 60 nm to 100 nm, such as 60 nm, 70 nm, 80 nm, 90 nm, or 100 nm. In this invention, compared with Prussian blue and other types of materials, sodium titanium phosphate exhibits better long-term cycling stability (more than 30% increase in stable cycle count); furthermore, by further controlling its particle size within the range of 20 to 50 nm, the number of adsorption active sites can be increased, the ion transfer and adsorption rates can be accelerated, the volume change stress during cycling can be alleviated, and it is also beneficial for the contact and uniform mixing of conductive polymers.

[0030] Preferably, the sodium titanium phosphate is prepared by the following method: titanium nanotubes and sodium dihydrogen phosphate are mixed and ground, then an aqueous solution of phosphoric acid is added, and grinding is continued until a white slurry is formed. Then, a hydrothermal reaction is carried out, and finally the solid product is annealed to obtain the sodium titanium phosphate.

[0031] Preferably, the temperature of the hydrothermal reaction is 140℃~160℃, such as 140℃, 145℃, 150℃, 155℃ or 160℃, and the time is 8h~10h, such as 8h, 8.5h, 9h, 95h or 10h.

[0032] Preferably, the annealing temperature is 600℃~800℃, such as 600℃, 650℃, 700℃, 750℃ or 800℃, and the time is 5h~7h, such as 5h, 5.5h, 6h, 6.5h or 7h.

[0033] Preferably, the solid product is washed and dried sequentially before the annealing treatment.

[0034] Preferably, the second mixing method includes ultrasound.

[0035] Preferably, the pH of the second mixture is 1 to 3, such as 1, 2 or 3.

[0036] Preferably, the third mixing method includes: adding a conductive polymer monomer to the second mixture and ultrasonically treating it for 20 min to 40 min to obtain the third mixture, wherein the ultrasonic time is, for example, 20 min, 25 min, 30 min, 35 min or 40 min.

[0037] Preferably, the fourth mixing process includes adding an oxidant solution to the third mixture under ice bath conditions.

[0038] Preferably, the rate at which the oxidant solution is added is 0.2 mL / s to 0.4 mL / s, for example, 0.2 mL / s, 0.25 mL / s, 0.3 mL / s, 0.35 mL / s, or 0.4 mL / s.

[0039] Preferably, the temperature of the ice bath is 0℃~4℃, for example, 0℃, 1℃, 2℃, 3℃ or 4℃.

[0040] Preferably, the in-situ polymerization reaction is carried out at a temperature of 0°C to 4°C and for a time of 5h to 7h. For example, the temperature is 0°C, 1°C, 2°C, 3°C or 4°C, and the time is 5h, 5.5h, 6h, 6.5h or 7h.

[0041] Preferably, the in-situ polymerization reaction is carried out under stirring.

[0042] Preferably, the product after the in-situ polymerization reaction is subjected to solid-liquid separation, washing, and drying in sequence.

[0043] Preferably, the first mixing method includes: dispersing the conductive polymer-coated Faraday material in water to obtain a first dispersion; dispersing the MXene material in water to obtain a second dispersion; and then mixing the first dispersion and the second dispersion in a fifth mixing process.

[0044] Preferably, the concentration of the first dispersion is 2 mg / mL to 4 mg / mL, such as 2 mg / mL, 2.5 mg / mL, 3 mg / mL, 3.5 mg / mL or 4 mg / mL.

[0045] Preferably, the concentration of the second dispersion is 0.5 mg / mL to 1.5 mg / mL, for example, 0.5 mg / mL, 0.8 mg / mL, 1 mg / mL, 1.2 mg / mL or 1.5 mg / mL.

[0046] Preferably, the fifth mixture is subjected to centrifugation and freeze-drying in sequence.

[0047] Preferably, the freeze-drying temperature is -10°C to -50°C, and the time is 12h to 36h. For example, the temperature is -10°C, -20°C, -30°C, -40°C or -50°C, and the time is 12h, 15h, 20h, 25h, 30h or 36h.

[0048] Preferably, the freeze-drying is carried out in a vacuum, and the vacuum degree is 1.3 Pa to 13 Pa, such as 1.3 Pa, 3 Pa, 5 Pa, 8 Pa, 10 Pa or 13 Pa.

[0049] Thirdly, the present invention also provides an electrochemical desalination composite electrode, wherein the electrochemical desalination composite electrode comprises the composite electrode material described in the first aspect.

[0050] Preferably, the separation factor of the electrochemical desalination composite electrode for lithium ions and magnesium ions is ≥0.91.

[0051] The numerical range described in this invention includes not only the point values ​​listed above, but also any point values ​​within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in the range.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] In the composite electrode material provided by this invention, the conductive polymer, Faraday material and MXene material work synergistically to achieve charge-matched molecular-level composite and in-situ construction of a conductive network, which significantly improves the desalination capacity and cycle stability of the composite material when used for electrochemical desalination. Furthermore, the preparation method provided by this invention is simple and can achieve low-temperature controllable synthesis of the material, making it suitable for large-scale applications. Attached Figure Description

[0054] Figure 1 This is a SEM image of the composite electrode material prepared in Example 1.

[0055] Figure 2 This is the XRD pattern of the composite electrode material prepared in Example 1. Detailed Implementation

[0056] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0057] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification and claims of this application are intended to cover non-exclusive inclusion.

[0058] It should be noted that the average particle size of sodium titanium phosphate used in Examples 1-6, Examples 8-9, and Comparative Examples 1-3 is 80 nm. It is synthesized using titanium nanotubes (TiNTs) as a precursor via a hydrothermal method and then annealed. The titanium nanotubes were prepared according to the method disclosed by Dawson G. et al. (doi:10.1016 / j.solidstatesciences.2010.09.019).

[0059] The specific steps are as follows: Accurately weigh 300 mg of titanium nanotubes and 300 mg of sodium dihydrogen phosphate, and grind them thoroughly in an agate mortar. Then, add 1 mL of deionized water and 1 mL of phosphoric acid to the mortar, and continue grinding until a white slurry is formed. Divide the resulting slurry into three equal portions, and transfer each portion to a 50 mL sealed polytetrafluoroethylene liner. React the slurry in an oven at 150°C for 9 hours.

[0060] After the reaction, the white product was centrifuged (5000 rpm, 5 minutes each time) several times until the supernatant was clear. The washing solution used was deionized water. The washed precipitate was then dried in a 90°C oven for 24 hours. Finally, the dried solid was ground into powder and annealed at 700°C under argon protection at a programmed heating rate of 5°C / min for 6 hours.

[0061] Example 1

[0062] This embodiment provides a composite electrode material for electrochemical desalination, comprising polyaniline-coated sodium titanium phosphate nanoparticles and Ti3C2T x MXene material, in which polyaniline-coated sodium titanium phosphate nanoparticles and Ti3C2T x The MXene material had a mass ratio of 2:1, and the coating thickness was 6.5 nm. The preparation method is as follows:

[0063] (1) Preparation of conductive polymer-coated Faraday material: 50 mg sodium titanium phosphate and 30 mL of 50% phytic acid solution were added to a 50 mL centrifuge tube and sonicated for 10 min; then 0.137 mL of aniline monomer (mass ratio of aniline monomer to sodium titanium phosphate was 3:1) was added to the mixture and sonicated for another 30 min; then 4.278 g of ammonium persulfate was dissolved in 15 mL of deionized water to form a solution, which was slowly added to the above premixed solution under 0℃ ice bath conditions. After stirring continuously at 0℃ for 6 h, the obtained dispersion was filtered, the obtained solid was washed three times with deionized water, and finally dried in an oven overnight to obtain the conductive polymer-coated Faraday material;

[0064] (2) Preparation of a composite of conductive polymer-coated Faraday material and MXene material: Take an appropriate amount of conductive polymer-coated Faraday material and mix it with deionized water, and sonicate for 10 min to obtain a dispersion A with a concentration of 2 mg / mL. Dilute MXene with deionized water to obtain an MXene dispersion B with a concentration of 1 mg / mL. Mix the two dispersions at a volume ratio of 1:1, centrifuge the mixture, collect the lower precipitate, and freeze-dry it to obtain the final product.

[0065] Example 2

[0066] This embodiment provides a composite electrode material for electrochemical desalination, comprising polyaniline-coated sodium titanium phosphate nanoparticles and Nb2CT. x MXene material, in which polyaniline-coated sodium titanium phosphate nanoparticles and Nb2CT x The MXene material had a mass ratio of 2:1 and a coating thickness of 4 nm. The preparation method is as follows:

[0067] (1) Preparation of conductive polymer-coated Faraday material: 50 mg of sodium titanium phosphate and 30 mL of 37% hydrochloric acid solution were added to a 50 mL centrifuge tube and sonicated for 10 min; then 0.091 mL of aniline monomer (mass ratio of aniline monomer to sodium titanium phosphate was 2:1) was added to the mixture and sonicated for another 30 min; then 2.852 g of ammonium persulfate was dissolved in 15 mL of deionized water to form a solution, which was slowly added to the above premixed solution under ice bath conditions at 2 °C. After stirring continuously at 2 °C for 5 h, the obtained dispersion was filtered, the resulting solid was washed three times with deionized water, and finally dried in an oven overnight to obtain the conductive polymer-coated Faraday material.

[0068] (2) Preparation of a composite of conductive polymer-coated Faraday material and MXene material: Take an appropriate amount of conductive polymer-coated Faraday material and mix it with deionized water, and sonicate for 10 min to obtain a dispersion A with a concentration of 3 mg / mL. Dilute MXene with deionized water to obtain an MXene dispersion B with a concentration of 1 mg / mL. Mix the two dispersions at a volume ratio of 1:1, centrifuge the mixture, collect the lower precipitate, and freeze-dry it to obtain the final product.

[0069] Example 3

[0070] This embodiment provides a composite electrode material for electrochemical desalination, comprising polyaniline-coated sodium titanium phosphate nanoparticles and Mo2CT. x MXene material, in which polyaniline-coated sodium titanium phosphate nanoparticles and Mo2CT x The MXene material had a mass ratio of 2:1 and a coating thickness of 9 nm. The preparation method is as follows:

[0071] (1) Preparation of conductive polymer-coated Faraday material: 50 mg of sodium titanium phosphate and 30 mL of 50% toluenesulfonic acid solution were added to a 50 mL centrifuge tube and sonicated for 10 min. Then, 0.182 mL of aniline monomer (mass ratio of aniline monomer to sodium titanium phosphate was 4:1) was added to the mixture and sonicated for another 30 min. 4.055 g of ferric chloride was dissolved in 15 mL of deionized water to form a solution, which was then slowly added to the premixed solution under ice bath conditions at 4 °C. After stirring continuously at 4 °C for 7 h, the obtained dispersion was filtered, and the resulting solid was washed three times with deionized water. Finally, it was dried in an oven overnight to obtain the conductive polymer-coated Faraday material.

[0072] (2) Preparation of a composite of conductive polymer-coated Faraday material and MXene material: Take an appropriate amount of conductive polymer-coated Faraday material and mix it with deionized water, and sonicate for 10 min to obtain a dispersion A with a concentration of 3 mg / mL. Dilute MXene with deionized water to obtain an MXene dispersion B with a concentration of 1 mg / mL. Mix the two dispersions at a volume ratio of 1:1, centrifuge the mixture, collect the lower precipitate, and freeze-dry it to obtain the final product.

[0073] Example 4

[0074] The difference between this embodiment and Example 1 is that the mass ratio of the polyaniline-coated sodium titanium phosphate nanoparticles to the MXene material is 3:1; in step (2), the concentration of dispersion A is adjusted to 3 mg / L.

[0075] The remaining preparation methods and parameters are consistent with those in Example 1.

[0076] Example 5

[0077] The difference between this embodiment and Example 1 is that the mass ratio of the polyaniline-coated sodium titanium phosphate nanoparticles to the MXene material is 1:1; in step (2), the concentration of dispersion A is adjusted to 1 mg / L.

[0078] The remaining preparation methods and parameters are consistent with those in Example 1.

[0079] Example 6

[0080] The difference between this embodiment and Example 1 is that the mass ratio of polyaniline-coated sodium titanium phosphate nanoparticles to MXene material is 4:1; in step (2), the concentration of dispersion A is adjusted to 4 mg / L.

[0081] The remaining preparation methods and parameters are consistent with those in Example 1.

[0082] Example 7

[0083] The difference between this embodiment and Embodiment 1 is that sodium titanium phosphate is replaced with Prussian blue Ti3C2 MXene;

[0084] The remaining preparation methods and parameters are consistent with those in Example 1.

[0085] Example 8

[0086] The difference between this embodiment and Example 1 is that polyaniline is replaced with polypyrrole; in step (1), 0.137 mL of aniline monomer is replaced with 0.104 mL of pyrrole monomer;

[0087] The remaining preparation methods and parameters are consistent with those in Example 1.

[0088] Example 9

[0089] The difference between this embodiment and Example 1 is that the thickness of the polyaniline coating is 20 nm; and step (1) involves adding 0.411 mL of aniline monomer.

[0090] The remaining preparation methods and parameters are consistent with those in Example 1.

[0091] Example 10

[0092] The difference between this embodiment and Example 1 is that the sodium titanium phosphate was purchased directly (Zhongke Experiment), and the average particle size was 50µm;

[0093] The remaining preparation methods and parameters are consistent with those in Example 1.

[0094] Comparative Example 1

[0095] The difference between this comparative example and Example 1 is that the composite electrode material for electrochemical desalination is sodium titanium phosphate; steps (1) and (2) were not performed.

[0096] Comparative Example 2

[0097] The difference between this comparative example and Example 1 is that the composite electrode material for electrochemical desalination is polyaniline-coated sodium titanium phosphate nanoparticles; step (2) was not performed.

[0098] The remaining preparation methods and parameters are consistent with those in Example 1.

[0099] Comparative Example 3

[0100] The difference between this comparative example and Example 1 is that the composite electrode material for electrochemical desalination is a composite of sodium titanium phosphate nanoparticles and MXene material; step (1) is omitted, and in step (2), the polymer-coated Faraday material is replaced with sodium titanium phosphate.

[0101] The remaining preparation methods and parameters are consistent with those in Example 1.

[0102] Structural characterization

[0103] The composite electrode material prepared in Example 1 was subjected to SEM and XRD tests, respectively. The test results are as follows: Figure 1 and Figure 2 As shown.

[0104] Performance testing

[0105] (1) Preparation of composite material electrodes

[0106] The samples prepared in Examples 1-10 and Comparative 1-3, conductive carbon black, and PVDF binder were mixed at a mass ratio of 8:1:1 (sample: carbon black: polyvinylidene fluoride (PVDF)), and a small amount of N-methylpyrrolidone (NMP) solvent was added to prepare a slurry. The slurry was coated onto graphite paper and dried under vacuum at 80°C to obtain the composite electrode.

[0107] (2) Test the deionization performance of the capacitor

[0108] The capacitive deionization device is assembled sequentially from the base plate, composite material electrode, cation exchange membrane, water flow baffle, anion exchange membrane, activated carbon electrode, and back to the base plate. The base plate at both ends has inlet and outlet ports. The capacitive deionization device, water collection tank, and peristaltic pump are connected by flexible hoses; a conductivity testing probe is placed in the water collection tank; the electrodes at both ends and the battery testing system are connected by wires to form the capacitive deionization testing system. During operation, sodium chloride brine flows from the water collection tank to the capacitive deionization device via the peristaltic pump and then back to the water collection tank. The battery testing system provides a constant current density to charge and discharge the electrodes, controlling the adsorption or desorption of ions by the electrodes. Simultaneously, the conductivity meter measures the change in the conductivity of the aqueous solution.

[0109] On the one hand, the composite material electrodes prepared in Example 1 and Comparative Examples 1-2 were tested while maintaining a sodium chloride solution concentration of 750 mg / L and a current density of 30-100 mA / g. On the other hand, the composite material electrodes prepared in Example 1 and Comparative Examples 1-2 were tested while maintaining a current density of 30 mA / g and a sodium chloride solution concentration of 250-750 mg / L. The sodium ion adsorption capacity of the sodium chloride solution was calculated, and the results are shown in Table 1. In addition, the composite material electrodes prepared in Examples 2-10 and Comparative Example 3 were tested under the condition of a sodium chloride solution concentration of 750 mg / L and a current density of 30 mA / g. The sodium ion adsorption capacity of the sodium chloride solution was calculated, and the results are shown in Table 2.

[0110] The adsorption capacity calculation formula is as follows: ;

[0111] V represents the volume of the sodium chloride solution in L; C0 represents the initial lithium concentration in the feed solution in g / L; C represents the lithium concentration in the discharge solution in g / L; and m represents the mass of the anode material in g.

[0112] (3) Cyclic stability test

[0113] The capacity was evaluated by performing 100 charge-discharge cycles in an aqueous sodium chloride solution with an initial concentration of 750 mg / L. The current density was set to 100 mA / g, and the voltage range was -1.4 V to +1.4 V. The results are shown in Table 3, where the capacity retention rate after 100 cycles is calculated as (capacity at the 100th cycle / initial capacity) × 100%.

[0114] Table 1

[0115]

[0116] Table 2

[0117]

[0118] Table 3

[0119]

[0120] As shown in Tables 1 and 2, the composite electrode material for electrochemical desalination provided by this invention exhibits a sodium ion adsorption capacity of over 141.24 mg / g for sodium chloride solution under different test conditions. In particular, Example 1 shows an adsorption capacity as high as 255.85 mg / g in a sodium chloride solution with an initial concentration of 750 mg / L and a charging condition of 30 mA / g, which is three times that of the sodium titanium phosphate electrode (Comparative Example 1), demonstrating excellent adsorption performance. As shown in Table 3, the composite electrode material for electrochemical desalination provided by this invention maintains a capacity retention rate of up to 100% after 100 cycles, significantly higher than that of Comparative Examples 1-3. The absence of conductive polymers and MXene in the electrode materials of Comparative Example 1, Comparative Example 2, and Comparative Example 3 all resulted in varying degrees of decrease in the sodium ion adsorption capacity and cycling performance of the materials for sodium chloride solution.

[0121] A comparison of the data from Examples 1 and 4-10 shows that in the composite electrode material provided by the present invention, the mass ratio of the conductive polymer-coated Faraday material to MXene, the mass ratio of the Faraday material to the conductive polymer material, the types of the Faraday material and the conductive polymer material, and the particle size of the Faraday material all affect the performance of the material. By controlling these within the preferred range provided by the present invention, the performance of the composite electrode material can be improved.

[0122] Depend on Figure 1 It can be seen that in the composite material prepared by this invention, the particle size of sodium titanium phosphate is approximately 80 nm, and it is coated with a polyaniline layer approximately 7 nm thick. A layer of MXene material exists between two polyaniline-coated sodium titanium phosphate nanoparticles. Figure 2 It can be seen that whether it is coated with polyaniline (Comparative Example 2) or coated and then combined with MXene (Example 1), the crystal structure of sodium titanium phosphate remains unchanged and is still the same as that of pure sodium titanium phosphate particles (Comparative Example 1).

[0123] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A composite electrode material for electrochemical desalination, characterized in that, The composite electrode material includes a conductive polymer-coated Faraday material and an MXene material, which are self-assembled by electrostatic forces. In the Faraday material coated with the conductive polymer, the coating thickness of the conductive polymer is 4 nm to 9 nm. The MXene material includes Ti3C2T. x MXene, Ta4C3T x MXene, Ti2CT x MXene, Nb4C3T x MXene, Nb2CT x MXene, V2CT x MXene or Mo2CT x Any one or at least two combinations of MXene, where T x It is a functional group, including any one of -O, -OH, -F or -Cl; The conductive polymer includes polyaniline and / or polypyrrole; The method for preparing the composite electrode material includes: initiating the polymerization of conductive polymer monomers on the surface of a Faraday material through an in-situ polymerization reaction to obtain a Faraday material coated with a conductive polymer, then performing a first mixing with MXene material, and finally self-assembling the composite electrode material under electrostatic force. The in-situ polymerization reaction includes: firstly, a second mixing of a Faraday material and an acidic solution to obtain a second mixture, and then a third and fourth mixing of a conductive polymer monomer and an oxidant solution in sequence, and after the in-situ polymerization reaction, the Faraday material coated with the conductive polymer is obtained; The Faraday material includes any one or a combination of at least two of sodium titanium phosphate, titanium phosphate, titanium pyrophosphate, sodium aluminum titanium phosphate, sodium vanadium phosphate, or Prussian blue. The pH of the second mixture is 1 to 3.

2. The composite electrode material for electrochemical desalination according to claim 1, characterized in that, The conductive polymer is polyaniline.

3. The composite electrode material for electrochemical desalination according to claim 1, characterized in that, The mass ratio of the conductive polymer-coated Faraday material to MXene material is (1~3):

1.

4. A method for preparing a composite electrode material as described in any one of claims 1-3, characterized in that, The preparation method includes: initiating the polymerization of conductive polymer monomers on the surface of a Faraday material through an in-situ polymerization reaction to obtain a Faraday material coated with a conductive polymer, then performing a first mixing with MXene material, and finally self-assembling the composite electrode material under electrostatic force. The in-situ polymerization reaction includes: firstly, a second mixing of a Faraday material and an acidic solution to obtain a second mixture, and then a third and fourth mixing of a conductive polymer monomer and an oxidant solution in sequence, and after the in-situ polymerization reaction, the Faraday material coated with the conductive polymer is obtained; The Faraday material includes any one or a combination of at least two of sodium titanium phosphate, titanium phosphate, titanium pyrophosphate, sodium aluminum titanium phosphate, sodium vanadium phosphate, or Prussian blue. The pH of the second mixture is 1 to 3.

5. The preparation method according to claim 4, characterized in that, The Faraday material is sodium titanium phosphate.

6. The preparation method according to claim 4, characterized in that, The Prussian blue comprises any one or a combination of at least two of Na2Mn[Mn(CN)6], Fe4[Fe(CN)6]3, or Na2M[Fe(CN)6], wherein the M in Na2M[Fe(CN)6] comprises any one or a combination of at least two of Ni, Cu, Zn, or Fe.

7. The preparation method according to claim 4, characterized in that, The acidic solution comprises an acid and a solvent, wherein the acid comprises any one or a combination of at least two of hydrochloric acid, phytic acid, or p-toluenesulfonic acid.

8. The preparation method according to claim 4, characterized in that, The oxidant solution comprises an oxidant and water, wherein the oxidant comprises ammonium persulfate and / or ferric chloride.

9. The preparation method according to claim 4, characterized in that, The mass ratio of the conductive polymer monomer to the Faraday material is (2~4):

1.

10. The preparation method according to claim 8, characterized in that, The molar ratio of the oxidant to the conductive polymer monomer is 1:(1~2).

11. The preparation method according to claim 4, characterized in that, The average particle size of the sodium titanium phosphate is 60 nm to 100 nm.

12. The preparation method according to claim 4, characterized in that, The sodium titanium phosphate is prepared by the following method: titanium nanotubes and sodium dihydrogen phosphate are mixed and ground, then an aqueous solution of phosphoric acid is added, and grinding is continued until a white slurry is formed. Then, a hydrothermal reaction is carried out, and finally the solid product is annealed to obtain the sodium titanium phosphate.

13. The preparation method according to claim 4, characterized in that, The third mixing method includes: adding a conductive polymer monomer to the second mixture and ultrasonically treating it for 20 min to 40 min to obtain the third mixture.

14. The preparation method according to claim 4, characterized in that, The fourth mixing process includes adding an oxidant solution to the third mixture under ice bath conditions.

15. The preparation method according to claim 14, characterized in that, The temperature of the ice bath is 0℃~4℃.

16. The preparation method according to claim 4, characterized in that, The in-situ polymerization reaction is carried out at a temperature of 0℃ to 4℃ for a duration of 5h to 7h.

17. The preparation method according to claim 4, characterized in that, The in-situ polymerization reaction is carried out under stirring.

18. The preparation method according to claim 4, characterized in that, The product after the in-situ polymerization reaction was subjected to solid-liquid separation, washing, and drying in sequence.

19. The preparation method according to claim 4, characterized in that, The first mixing method includes: dispersing the conductive polymer-coated Faraday material in water to obtain a first dispersion; dispersing the MXene material in water to obtain a second dispersion; and then mixing the first dispersion and the second dispersion in a fifth mixing process.

20. The preparation method according to claim 19, characterized in that, The concentration of the first dispersion is 2 mg / mL to 4 mg / mL.

21. The preparation method according to claim 19, characterized in that, The concentration of the second dispersion is 0.5 mg / mL to 1.5 mg / mL.

22. The preparation method according to claim 19, characterized in that, The fifth mixture was then subjected to centrifugation and freeze-drying in sequence.

23. An electrochemical desalination composite electrode, characterized in that, The electrochemical desalination composite electrode comprises the composite electrode material according to any one of claims 1-3.

Citation Information

Patent Citations

  • Prussian blue composite nanomaterial as well as preparation method and application thereof

    CN119191482A

  • Preparation method and application of ammonium ion pre-embedded Cu-MOF-derived CuHCF / MXene electrode material

    CN119285047A

  • Sodium ion composite positive electrode material and preparation method and application thereof

    CN115642237A